Distance education during the pandemic generated by COVID- 19 in Latin America (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A documentary review of the scientific production registered in the Scopus database on thestudy of Digital Distance Education in the COVID-19 pandemic in Latin America wascarried out with the purpose of knowing the main characteristics of the generation of newknowledge on this topic. The information analyzed is provided by Scopus through itsSearch tool, by means of which the data is filtered in such a way that a total of 178 researchpapers published in high impact journals are obtained, referring to distance educationduring the COVID-19 pandemic. Due to its nature, the temporal delimitation is defined bythe two semesters of 2020 and the first semester of 2021, at the date of the present research.The bibliometric review is performed on the basis of these data, which are classifiedaccording to their area of knowledge, country of origin and affiliation. Once theinformation is classified, certain papers are analyzed from a bibliographic perspective toknow and define the position of different authors with respect to the proposed topic.